Physical recovery after laparoscopic vs. open liver resection – A prospective cohort study. (December 2019) - Kampf, S.; Sponder, M.; Bergler-Klein, J.; Sandurkov, C.; Fitschek, F.; Bodingbauer, M.; Stremitzer, S.; Kaczirek, K.; Schwarz, C.
Abstract: Background: While the number of laparoscopic liver resections (LLRs) is increasing worldwide, its impact on physical recovery remains unclear. We hypothesized that LLR is associated with better physical recovery than open liver resection (OLR). To address this question, we investigated the impact of laparoscopic liver resection compared to open liver resection on physical recovery in a prospective trial. Methods: Twenty-one patients who underwent LR were included in this study (11 OLR (52.4%) and 10 LLR (47.6%), respectively). Physical recovery was measured by bicycle stress testing at months 1 and 6 after surgery and compared to preoperative stress testing. Standardized performance for bicycle stress testing was calculated based on age, sex, height and weight. Physical recovery was compared between groups as change of performance (%). Results: Median age was 58 years (Inter Quartile Range (IQR): 44–68), and the main indications for LR were colorectal liver metastases (n = 10; 45%) and hepatocellular carcinoma (n = 6; 27%). The one-month change of performance level was −8% (IQR: -12-1) compared to the preoperative level with no significant difference between open and laparoscopic LR (LLR: -8% (-11 – 1); OLR: -6% (-12 – 4), p = 0.833). Furthermore, 6 months postoperatively, patients in both groups had not reached back their preoperative performance level (LLR: -5.7% (−8.4 - 18.6); OLR -4. 8% (−12.6 - 1.9), p = 0.833). Conclusion: In this study, we report an impaired physical recovery after LR that was not fully restored 6 months after surgery. There was no significant difference between open and laparoscopic LR in terms of bicycle stress testing. Limitations of the study include the limited sample size and differences, albeit non-statistically significant, in the baseline characteristics of the two groups. To rule out a possible role of age or underlying indication for liver resection on physical recovery, future randomized controlled trials need to be performed. Highlights: One of the first prospective trials considering recovery after laparoscopic vs open liver resection. Patients with major laparoscopic liver resections tended to have better physical performance 1 month after surgery. Faster recovery after surgery could be an advantage for patients with metastatic disease awaiting postoperative chemotherapy.